미취학 아동의 미디어 사용과 아동의 기질, 양육 스트레스와의 관계 - 김동희(Dong Hee Kim) (Seuteureseu yeon-gu (Online), 2014)
본 연구는 미취학 아동의 미디어 사용 실태와 아동의 기질 어머니의 양육 스트레스와의 관계를 확인하기 위해 시행되었다. 편의 표집된 서울 및 경기 지역의 개인 크리닉 다섯 곳에 예방접종을 위해 내원한 건강한 미취학 아동과어머니 중 연구에 참여하기로 동의한 어머니 196명을 대상으로 아동의 기질, 양육 스트레스 측정도구를 사용하여자료수집하였다. 수집된 자료는 기술통계, t-test, ANOVA, correlation coefficient를 이용하여 분석하였다. 미디어 기기중 TV를 가장 많이 보고 대상자 모두 2가지 이상의 미디어 기기를 사용하였다. 미디어 총 사용시간은 하루 평균3.36시간이었고 주로 동영상을 보았으며 게임과 학습을 위해 사용하였다. 엄마가 고등학교 졸업 이하인 경우 가장많이 미디어에 노출 되었다. 아동의 기질 중 생리적 규칙에서 TV와 스마트기기의 사용시간이 음의 상관관계(r= −0.175, p=＜.05)를 보였고 총 미디어 사용 시간에서도 유의미한 음의 상관관계(r=−0.246, p=＜.01)를 나타냈다. 양육 스트레스와 총 미디어 사용 시간과는 양의 상관관계가 있는 것으로 나타났다(r=0.815, p=＜.05). 올바른 미디어사용을 위해 부모와 자녀 대상의 미디어 사용 태도와 방법에 대한 교육이 필요하며 특히 어머니의 양육 스트레스가높을수록 미디어 사용 시간이 많아지므로 자녀 양육 시 스트레스를 경험할 때 미디어 기기에 의존하는 것이 아니라자녀의의 다양한 상호작용 방법을 포함한 양육 방법에 대한 교육을 제공해야 할 것이다. The objective of this study was to identify the relationships between a child’s media use, a child’s temperament, and parenting stress. Data were collected from 196 mothers of preschool children with self-reported questionnaires; a temperament rating scale, parenting stress index (PSI). Analysis was performed by Descriptive, T-test, ANOVA, and Pearson correlation analyses were performed. TV was the most frequently used media and most participants used more than 2 types of media. The total hours of media use were 3.36 hours. Video viewing, learning, and games were the most common purposes of media usage. The mother’s education level correlated with the hours of use; when the level was high school or below, the child was exposed to media for longer. There was a significant relationship between the total hours of media use and a child’s temperament (r=−0.246, p=＜.01). There was also a relationship between hours of media use and parenting stress (r=0.815, p=＜.05). In conclusion, a program is needed to educate parents and children about proper media usage. It is especially important to provide interventions to promote parenting skills, including alternative interactions when mothers experience parenting stress. KCI Citation Count: 13